A comparative study of the usability of touch-based and mouse-based interaction. Issue 1 (1st April 2014) - Travis, Charlotte; Murano, Pietro
Abstract : Purpose: – This paper is about an investigation into the usability of touch-based user interfaces. Currently, not enough knowledge is available to guide user interface designers and developers concerning the appropriate use of touch-based technology. The paper aims to discuss these issues. Design/methodology/approach: – The authors adopt an empirical approach using an experiment to test the effectiveness and user satisfaction of touch-based interaction compared with equivalent mouse-based interaction. The authors had two abstract type tasks and one contextualised task using the two methods of interaction. The authors measured errors, task time and user satisfaction. Findings: – The data were statistically analysed and the statistically significant results show that overall the mouse-based interaction was faster, caused fewer errors and was preferred by the participants. Originality/value: – These results are interesting for all user interface designers and developers, where the authors make some design suggestions based on the empirical results. The results also add to the current knowledge the authors have regarding interaction with touch interfaces. Further, the authors also propose ways forward to enrich this research area of further knowledge.